Evaluasi Standar Operasional Prosedur Dan Pola Sirkulasi Pengunjung Museum Tjong A Fie: Kajian Historic House Museum - Charisma Sembiring, Devy (Humanis, 2018)
Museum Tjong A Fie is one of the museum located in Medan City, North Sumatera. This museum was originally a residence of historical figures in the development of the city of Medan is Tjong A Fie originating from China. Museum Tjong A Fie has been designated as a cultural heritage building and used as a museum. This research will discuss Standard Operating Procedures and Visitor Circulation Pattern of Tjong A Fie Museum as a part that must be considered in the organization of the museum. The author uses data collection methods such as observation, interview and literature study and data processing methods through qualitative and comparative analysis. The theory used to refine the interpretation of the results of analysis is Management Theory. Based on the results of research found that the Museum Tjong A Fie has no SOP according to the standard and mandate of PP No. 66 Year 2015. Circulation pattern shows two circulation patterns are unstructured and structured. The recommendations offered include the need to develop SOPs in accordance with the mandate of museum legislation and governance.